Auditing & assurance services : - Messier, William F. (McGraw - Hill, 2006)
The book sets each chapter up in an understandable, and digestable way.The tables and charts are excellent summaries of the reading and it is entirely possible to just skip the reading and memorize those. Each chapter has thought-provoking...